Comparative study on mechanical performance of photocurable acrylate coatings with bio-based versus fossil-based components. (August 2022) - Samyn, Pieter; Bosmans, Joey; Cosemans, Patrick
Abstract: The UV curing of acrylate coatings offers favourable protection of wood surfaces against mechanical damage while their performance can be tuned depending on the selection of monomers, oligomers and photocuring conditions. The aim for more sustainable organic coatings increased the willingness for substituting fossil-based into bio-based resources, but the performance of both alternatives needs to be validated to promote their applicability. In this research, a range of acrylate monomers and oligomers with different functionality and analogous composition of both bio-based and fossil-based grades was applied as a coating on soft- and hardwood substrates under similar photochemical conditions. The coatings were evaluated in terms of mechanical performance (Taber abrasive wear resistance, scratch resistance, hardness) and physico-chemical properties (gloss, hydrophobicity). Results systematically indicated a better abrasive wear resistance, scratch resistance and lower hardness of coatings with bio-based monomers or oligomers, in parallel with higher ductility and visco-elastic deformation. Also the gloss and hydrophobicity of bio-based coatings enhanced in parallel with formation of lubricating sliding patches in the wear track. This study confirms that bio-based coatings result in enhanced mechanical performance and provides evidence for their applicability as protective wood coatings. Graphical Abstract: ga1